Quality Control Acceptance Criteria Improvements for Pre-Stressed High Strength Concrete Pile Driving Operations in Japanese Building Construction - Kenneth* Bull; Juan Jose Castro; Kozo Nakada (Journal of Asian Architecture and Building Engineering, 2018)
The current practice in Japan for most driven pre-stressed high strength concrete (PHC) piling sites utilizes an ″energy formula″ approach involving the ″set-penetration test.″ In its current state, driven PHC piles in the Japanese construction industry are at increased risk of being damaged due to inferior driveability evaluation procedures leading to an increased probability of damaged piles remaining undetected after installation. This study presents two case studies in Okinawa, Japan which utilized dynamic analysis as the primary piling quality acceptance criteria and compares results to the energy formula approach which is more common to Japanese construction sites. Based on the observations of these two case studies, the applicability of dynamic testing, particularly the high-strain dynamic test, the low-strain integrity test, and wave equation analyses is analyzed. In conclusion, a case is presented that Japan′s over reliance on an energy formula approach should be augmented by additional QC procedures. A combination of wave equation analysis, dynamic testing and simple visual inspection of post-driven PHC pile conditions is recommended to better protect the integrity of driven PHC piles throughout Japan.